Simulation of an Antenna Array Factor Operating at the Wavelength of 0.21 m - Jallod, Uday E. (Iraqi Journal of Science, 2026)
This study involves examining the antenna array factor using the MATLAB environment for three types of antenna arrays. These types are carried out to operate at the neutral hydrogen line emission of the wavelength of 0.21 m (this wavelength is very important in radio astronomy observations) with three configurations of antenna arrays. These configurations are a linear array, a planar array, and a circular array. The array factor is computed to include the linear array factor (LAF), planar array factor (PAF), and circular array factor (CAF), respectively. The array configuration is considered a crucial parameter that controls an array factor pattern, and it depends on the number of antenna elements with the distance between elements. Therefore, four values for antenna element numbers were chosen to achieve the best results for the array factor. These element numbers (N) are taken to be 3,5,7, and 10. Then, the antenna number is fixed at N=10, with different separation distances (d) given in terms of wavelength, and equal to 0.25λ, 0.5λ, 0.75λ, and λ. The results indicate that the (LAF) with N=10 and d=0.75λ yields the most optimal performance, characterized by a narrow main lobe and reduced side lobes, as compared with PAF and CAF.